Information asymmetries and intra-company monitoring: An empirical analysis of nonlinear relationships between company characteristics and the size of the internal audit function - Marc Eulerich; Christian Lohmann (Schmalenbach Journal of Business Research (SBUR), 2022)
The internal audit function (IAF) has become one of the main pillars of good corporate governance. Empirical findings show that the size of the IAF varies considerably across companies. This study analyzes the relationships between selected company characteristics as determinants of intra-company information asymmetries and the size of the IAF as an indicator of intra-company monitoring. We test these relationships by analyzing comprehensive survey data obtained from chief audit executives from 283 Austrian, German, and Swiss companies. Using a~nonparametric regression approach, we identify significant nonlinear relationships between company characteristics and IAF size. The empirical analysis identifies threshold levels for several metric company characteristics, such as the number of employees and the number of subsidiaries, whose relationships with the size of the IAF change its intensity.
Keywords: 650; Company characteristics; Company size; Internal audit; Internal audit function; Nonparametric regression